PENGGUNAAN TEMBAGA SEBAGAI BAHAN CATALYTIC CONVERTER TERHADAP PERFORMA MESIN SEPEDA MOTOR SATRIA FU 150 - Muhammad Zaki; Abdul Ghofur; Sigit Mujiarto (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2018)
Many motorcycles increased within past few years, the gas emmited from the motorclyce will be polluted the population. One of technology that can reduce the emmited gas is using catalytic converter on the muffler. Catalytic converter is a catalyst that can alter or accelerate a matter (chemical reaction) of a carbon monoxide into carbon dioxide. In this research will use two types of catalytic converter that is honey comb and a copper plate. From the test can be seen that the catalytic converter with a honey comb shape better in terms of engine performance than the catalytic converter shaped plate. Compared wihtout any catalytic converter, the highest percentage honey comb catalyst reduce the power within 0.12 HP, and torque increased to 0.04 Nm. While the highest copper catalyst that reduce the power within 0.71 HP, and torque decreased to 0.2 Nm.